Mechanical interlocking polymer reinforced and toughened titanium carbide thin film material as well as preparation method and application thereof
By bridging the mechanical interlocking polymer on the titanium carbide film and using its intramolecular motion to enhance the toughness and stretchability of the material, the problem of insufficient elongation and toughness of the titanium carbide film material in the existing technology is solved, and high-performance materials are achieved. Strength, toughness and elongation of titanium carbide thin film materials.
Patent Information
- Application Number
- CN202411460934.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The prior art is difficult to achieve significant elongation and toughness in titanium carbide thin film materials, limiting its application in fields such as flexible electronics.
By using mechanical mutual lock molecules to react with co -polymer reactions to form a mechanical intermoder polymer, and the bridge is received on the carbide titanium -titanium thin film, the toughness and stretching of the titanium titanium -titanium -titanium -titanium -titanium -titanium -titanium titanium titanium are used.
The strength, toughness and elongation of the titanium carbide film are significantly improved, making it suitable for use in fields such as flexible electronics, wearable smart devices and wearable rehabilitation equipment.
Smart Images

Figure CN119331261A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of synthetic chemistry and nanocomposite material preparation, and in particular to a mechanically interlocking polymer reinforced and toughened titanium carbide film material, a preparation method and application thereof. Background Art
[0002] Titanium carbide (Ti3C2T X ) is a two-dimensional material with broad application prospects. Its excellent conductivity and mechanical properties make it popular in various fields, such as flexible electronics, supercapacitors, batteries, sensors and electromagnetic interference shielding. However, the preparation of titanium carbide nanosheets to high-performance macroscopic films is hindered by the inherent brittleness and inextensibility of the films, which limits the further application and development of titanium carbide materials. The rich hydroxyl functional groups on the surface of titanium carbide nanosheets can be used to regulate the interaction between the sheets. At present, most studies are on enhancing the tensile strength of titanium carbide film materials by introducing covalent / non-covalent bonds, but achieving significant elongation is still difficult to achieve. Summary of the invention
[0003] In order to solve the problems of the prior art, the purpose of the present invention is to overcome the shortcomings of the prior art and provide a mechanically interlocking polymer reinforced and toughened titanium carbide film material, a preparation method and an application thereof.
[0004] One of the purposes of the present invention is to provide a method for preparing a mechanically interlocked polymer reinforced and toughened titanium carbide film material, comprising the following steps:
[0005] S1. determining raw materials, including: mechanical interlocking molecules and copolymers, wherein the mechanical interlocking molecules contain one or more hydroxyl functional groups;
[0006] S2, reacting the mechanical interlocking molecules with the copolymer to extract a mechanical interlocking polymer;
[0007] S3, dissolving the mechanical interlocking polymer in an organic solvent to prepare a soaking solution, placing the titanium carbide film in the soaking solution for soaking treatment, and extracting to obtain the mechanical interlocking polymer bridged titanium carbide film.
[0008] Preferably, the molar ratio of the mechanically interlocking molecules to the copolymer is 1:(10-20).
[0009] In some preferred embodiments of the present invention, the mechanically interlocking molecule contains two hydroxyl functional groups.
[0010] Further preferably, the mechanically interlocked molecules are one or more of rotaxanes, catenanes, and daisy chains.
[0011] In some preferred embodiments of the present invention, the mechanically interlocked molecule is a hydroxyl-containing [2]rotaxane having the structural formula:
[0012]
[0013] In some preferred embodiments of the present invention, the mechanically interlocked molecule is a hydroxyl-containing catenane having the structural formula:
[0014]
[0015] In some preferred embodiments of the present invention, the mechanically interlocking molecule is a hydroxyl-containing daisy chain with the structural formula:
[0016]
[0017] Preferably, the copolymer is N,N'-carbonyldiimidazole.
[0018] Preferably, in S2, the mechanically interlocked molecules and the copolymer react in a reaction solvent under the following reaction conditions: stirring at room temperature, a stirring speed of 400 to 600 rpm, and a reaction time of 12 to 24 h.
[0019] More preferably, the ratio of the mechanically interlocked molecules to the reaction solvent is (100-500) mg: (10-20) mL.
[0020] In some preferred embodiments of the present invention, the ratio of the mechanically interlocked molecules to the reaction solvent is 20 mg / mL.
[0021] Further preferably, the reaction solvent is selected from dichloromethane, chloroform, toluene, tetrahydrofuran, acetonitrile, N,N-dimethylformamide.
[0022] In some preferred embodiments of the present invention, the reaction solvent is dichloromethane.
[0023] Preferably, the mechanical interlocking polymer is extracted by washing the reaction system of S2 with water for multiple times, removing water with anhydrous magnesium sulfate, and then removing dichloromethane.
[0024] Preferably, in S3, the concentration of the mechanical interlocking polymer in the soaking solution is 3 to 10 mg / mL.
[0025] In some preferred embodiments of the present invention, the usage ratio of the mechanical interlocking polymer and the organic solvent is 5 mg / mL.
[0026] Preferably, the organic solvent is selected from one or more of tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, dichloromethane, chloroform, and dimethyl sulfoxide.
[0027] In some preferred embodiments of the present invention, the organic solvent is selected from one of N,N-dimethylformamide, tetrahydrofuran and N,N-dimethylacetamide.
[0028] Preferably, the titanium carbide film is a self-supporting film prepared by vacuum filtration of a titanium carbide aqueous solution.
[0029] More preferably, the titanium carbide film has a thickness of 3 to 10 μm.
[0030] Further preferably, the usage ratio of the titanium carbide film and the immersion solution is (15-20) mg: (4-6) mL.
[0031] In some preferred embodiments of the present invention, the dosage ratio of the titanium carbide film to the immersion solution is 4 mg / mL.
[0032] Preferably, the soaking treatment is: soaking at 20-40° C. for 6-12 hours.
[0033] Further preferably, the soaking treatment is: soaking at 25-40° C. for 8-10 hours.
[0034] In some preferred embodiments of the present invention, the soaking treatment is: soaking at 25° C. for 10 hours.
[0035] In some preferred embodiments of the present invention, the soaking treatment is: soaking at 35° C. for 10 hours.
[0036] In some preferred embodiments of the present invention, the soaking treatment is: soaking at 40° C. for 8 hours.
[0037] Preferably, the mechanically interlocked polymer bridged titanium carbide film is extracted by washing with anhydrous ethanol and then drying.
[0038] More preferably, the drying treatment temperature is 40-60° C. and the vacuum drying is performed for 2-4 hours.
[0039] In some preferred embodiments of the present invention, the drying treatment is carried out at a temperature of 45° C., a vacuum degree of -0.1 MPa, and a time of 2 to 4 hours.
[0040] The second object of the present invention is to provide a mechanically interlocking polymer reinforced and toughened titanium carbide film material, which is prepared by the preparation method of the mechanically interlocking polymer reinforced and toughened titanium carbide film material.
[0041] Preferably, the surface of the film material is bridged with a mechanical interlocking polymer, wherein the mechanical interlocking polymer contains an ester functional group with an imidazole group.
[0042] The third object of the present invention is to provide a mechanically interlocking polymer reinforced and toughened titanium carbide thin film material for use in electronic products, wearable smart devices, and wearable rehabilitation equipment.
[0043] Preferably, the thin film material is used to prepare a stretchable electroluminescent device.
[0044] Further preferably, the thin film material is used to prepare an electrode layer of a stretchable electroluminescent device.
[0045] In some preferred embodiments of the present invention, the device comprises the thin film material, a polydioxyethylthiophene layer, and a zinc sulfide / copper / polydimethylsiloxane composite material layer located between the two layers.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] The present invention provides a method for preparing a mechanically interlocking polymer reinforced and toughened titanium carbide thin film material. A mechanically interlocking polymer is formed by the reaction between mechanically interlocking molecules and copolymers, and is bridged on the titanium carbide thin film material. The intramolecular movement of the mechanically interlocking molecules is utilized to achieve reinforcement and toughening of the titanium carbide thin film material. In addition to improving the strength and toughness, the elongation is also significantly improved.
[0048] The mechanically interlocked polymer reinforced and toughened titanium carbide film material prepared by the present invention is a material in which mechanically interlocked molecules are bridged to the surface of the titanium carbide film in the form of a copolymer. The mechanically interlocked molecules are a type of molecule with a special topological structure formed based on host-guest recognition using a molecular structure with spatial entanglement. Compared with traditional covalent bonds / non-covalent bonds, mechanically interlocked molecules can achieve controllable intramolecular motion, such as sliding, rotation, and translation. This special intramolecular motion mechanism gives the mechanically interlocked molecules dynamic stability and mechanical adaptability, so that the prepared titanium carbide film has excellent stretchability, especially while being repeatedly stretched, it can still have stable conductivity, and is suitable for application in the field of stretchable electronics, such as flexible electronic products, wearable smart devices, wearable rehabilitation equipment, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 The H-NMR spectrum of the mechanically interlocked polymer based on [2]rotaxane at 7.0-8.2 ppm;
[0050] Figure 2 This is a schematic diagram of the reaction of preparing a mechanically interlocked polymer using catenane in Example 2 of the present invention;
[0051] Figure 3 The H-NMR spectrum of catenane-based mechanically interlocked polymers at 7.0-8.2 ppm;
[0052] Figure 4 is the H NMR spectrum of the hydroxyl-containing daisy chain monomer prepared in Example 3 of the present invention;
[0053] Figure 5 This is a high-resolution mass spectrum of the hydroxyl-containing daisy chain monomer prepared in Example 3 of the present invention;
[0054] Figure 6 The H-NMR spectrum of the mechanically interlocked polymer based on the daisy chain at 7.0-8.3 ppm;
[0055] Figure 7 Schematic diagram of the structure of the stretchable electroluminescent device prepared in Example 4 of the present invention;
[0056] Figure 8 This is a macroscopic bending photograph of the RBM film prepared in Example 1 of the present invention;
[0057] Fig. 9 The scanning electron microscope morphology photograph (Figure a) and the energy dispersive spectrometer element analysis photograph of the RBM film prepared in Example 1 of the present invention, wherein Figure (b) corresponds to the Ti element, Figure (c) corresponds to the C element, and Figure (d) corresponds to the N element;
[0058] Fig.10 The tensile stress-strain curves of the titanium carbide film samples corresponding to Example 1, Comparative Example 1 and Comparative Example 3 of the present invention (Figure (a)), and the mechanical properties comparison diagram of the three samples (Figure (b)), including three performance directions of tensile strength, toughness and fracture strain;
[0059] Fig.11 The tensile stress-strain curves of the titanium carbide film samples corresponding to Example 1 and Comparative Example 2 of the present invention (Figure a), and the mechanical properties comparison diagram of the three samples (Figure b), including three properties of tensile strength, toughness and fracture strain;
[0060] Fig.12 The tensile stress-strain curves of the mechanically interlocked polymer-bridged titanium carbide films prepared in Example 2 (Figure a) and Example 3 (Figure b) of the present invention;
[0061] Fig.13 The relative resistance change of the RBM film prepared in Example 1 of the present invention when cyclically stretched 500 times in the strain range of 0-15%, R0 and R respectively represent the resistance of the RBM film before and after stretching;
[0062] Fig.14 These are luminescent photos of the stretchable electroluminescent device prepared in Example 4 of the present invention under tensile strains of 0%, 5%, 10%, 15% and 20%. DETAILED DESCRIPTION
[0063] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0064] Example 1
[0065] This embodiment provides a mechanically interlocked polymer reinforced and toughened titanium carbide film material, comprising the following steps:
[0066] S1. Identification of mechanically interlocked molecules
[0067] The mechanical interlocking molecule used in this embodiment is: hydroxyl-containing [2] rotaxane, the synthesis method is described in Angew.Chem.Int.Ed.2024,63,e202404481, and the structural formula is shown below:
[0068]
[0069] S2. Preparation of mechanically interlocked polymers
[0070] 200 mg of mechanical interlocking molecules were dissolved in 10 mL of dichloromethane, 250 mg of N,N'-carbonyldiimidazole was added, and the mixture was stirred at 25°C and 500 rpm for 20 hours. After the reaction was completed, the reaction system was repeatedly washed with water for 3-5 times, and then dried with anhydrous magnesium sulfate to remove water, and finally dichloromethane was removed to obtain a mechanical interlocking polymer. The reaction was as follows:
[0071]
[0072] like Figure 1 As shown, the H NMR spectrum of the mechanically interlocked polymer based on [2]rotaxane at 7.0-8.2 ppm shows the three characteristic signal peaks of the imidazole group. 1 , H 2 , H 3 They appeared at 8.14 ppm, 7.43 ppm and 7.07 ppm, respectively, thus proving the presence of an ester functional group with an imidazole group in the [2]rotaxane-based mechanically interlocked polymer.
[0073] S3. Dissolve 25 mg of the mechanical interlocking polymer prepared in S2 in 5 mL of N,N-dimethylformamide, take 5 mL to soak the titanium carbide film, soak it in a 40°C environment for 8 hours, and extract to obtain the [2] cycloalkane polymer bridged titanium carbide film, wherein the titanium carbide film is a self-supporting film prepared by vacuum filtration of a titanium carbide aqueous solution, and has a thickness of 5 μm.
[0074] The extraction method is: wash the polymer-bridged titanium carbide film obtained in S3 with anhydrous ethanol, and dry it in a vacuum oven at 45°C for 3 hours, wherein the vacuum degree of the vacuum oven is: -0.1MPa, to obtain [2] rotaxane polymer-bridged titanium carbide film, marked as: RBM.
[0075] Example 2
[0076] This embodiment provides a mechanically interlocked polymer reinforced and toughened titanium carbide film material, comprising the following steps:
[0077] S1. Identification of mechanically interlocked molecules
[0078] The mechanical interlocking molecule used in this embodiment is: a hydroxyl-containing catenane, the synthesis method of which is described in J.Am.Chem.Soc.2023,145,9011-9020, and the structural formula is shown below:
[0079]
[0080] S2. Preparation of mechanically interlocked polymers
[0081] 100 mg of the mechanical interlocking molecule was dissolved in 5 mL of dichloromethane, and 200 mg of N,N'-carbonyldiimidazole was added, and the mixture was stirred at 25°C and 500 rpm for 20 hours. After the reaction was completed, the reaction system was repeatedly washed with water for 3-5 times, and then dried with anhydrous magnesium sulfate to remove water, and finally dichloromethane was removed to obtain a mechanical interlocking polymer. The reaction was carried out as follows: Figure 2 As shown;
[0082] like Figure 3 As shown in the H NMR spectrum of the catenane-based mechanically interlocked polymer at 7.0-8.2 ppm, the three characteristic signal peaks of the imidazole group are 1 , H 2 , H 3 appeared at 8.15 ppm, 7.44 ppm and 7.08 ppm, respectively, thus proving the presence of an ester functional group with an imidazole group in the catenane-based mechanically interlocked polymer.
[0083] S3. Dissolve 30 mg of the mechanical interlocking polymer prepared in S2 in 6 mL of tetrahydrofuran, take 5 mL to soak the titanium carbide film, soak it in a 25°C environment for 10 hours, and extract to obtain a catenane polymer-bridged titanium carbide film, wherein the titanium carbide film is selected to be consistent with that in Example 1.
[0084] The extraction method is: wash the polymer-bridged titanium carbide film obtained in S3 with anhydrous ethanol, and dry it in a vacuum oven at 45°C for 2 hours, wherein the vacuum degree of the vacuum oven is: -0.1MPa, to obtain a catenane polymer-bridged titanium carbide film, marked as: CBM.
[0085] Example 3
[0086] This embodiment provides a mechanically interlocked polymer reinforced and toughened titanium carbide film material, comprising the following steps:
[0087] S1. Identification of mechanically interlocked molecules
[0088] The mechanical interlocking molecule used in this embodiment is a hydroxyl-containing daisy chain, and the structural formula is as follows:
[0089]
[0090] The synthesis method of daisy chain is as follows:
[0091] S1-1 Mix 5.5 mmol of 8-bromo-1-octanol, 5 mmol of p-hydroxybenzaldehyde, 7.5 mmol of potassium carbonate and 50 mL of N,N-dimethylformamide (DMF), and stir at 100°C and 500 rpm for 12 h. After the reaction, first remove DMF by rotary evaporation, and dissolve the crude product in dichloromethane (DCM), followed by water washing and extraction. Finally, dry the DCM organic phase with anhydrous magnesium sulfate (MgSO4), filter, and remove DCM by rotary evaporation to obtain product 3.1.
[0092]
[0093] S1-2, 27.4 mmol of 10-bromo-1-decene, 43.2 mmol of potassium phthalimide, 50 mL of tetrahydrofuran (THF) and 50 mL of DMF were mixed, and the mixture was refluxed at 80°C for 12 h. Then, 250 mL of ethanol (EtOH) and 2.5 g of hydrazine hydrate (N2H4·H2O) were added, and the mixture was refluxed at 80°C for 5 h. After the reaction, 10 mL of hydrochloric acid solution (6 M) was added, and after the solid was dissolved, sodium hydroxide solution (NaOH, 3 M) was added to adjust the pH to alkaline. The reaction system was then extracted with ethyl acetate. Finally, the ethyl acetate organic phase was dried over anhydrous MgSO4, filtered, and the ethyl acetate was removed by rotary evaporation to obtain the product 3.2.
[0094]
[0095] S1-3, mix 30 mmol of 3.1, 30 mmol of 3.2 and 250 mL of methanol (MeOH), react at 75°C for 24 h, then add 50 mmol of sodium borohydride (NaBH4), stir and react at room temperature and 500 rpm for 24 h, then add 50 mmol of di-tert-butyl dicarbonate ((Boc)2O) and 100 mL of DCM, stir and react at room temperature and 500 rpm for 24 h. After the reaction, add water to the system for extraction, then dry the DCM organic phase with anhydrous MgSO4, filter, and remove DCM by rotary evaporation to obtain a crude product, and finally purify it by column (eluent polar petroleum ether: ethyl acetate = 10:1 v / v) to obtain product 3.3.
[0096]
[0097] S1-4, 4.6 mmol of crown ether benzoic acid, 5.97 mmol of 3.3, 2.07 mmol of 4-dimethylaminopyridine (DMAP), 9.25 mmol of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) and 20 mL of DCM were mixed, and the mixture was stirred at room temperature and 500 rpm for 6 h. After the reaction, DCM was removed by rotary evaporation, and the solid was washed with ether to obtain the product 3.4.
[0098]
[0099] S1-5, 9.2 mmol of 3.4, 15 mmol of 9-borabicyclo[3.3.1]nonane (9-BBN) and 18 mL of THF were mixed, and the mixture was refluxed at 65°C for 6 h under nitrogen protection. Then 4 mL of EtOH, 6 mL of 4 M NaOH aqueous solution and 6 mL of hydrogen peroxide (H2O2) were added and mixed. Under nitrogen protection, the mixture was stirred at room temperature and 500 rpm for 12 h. After the reaction, THF was removed by rotary evaporation, and DCM and water were added for extraction. Finally, the DCM organic phase was dried over anhydrous MgSO4, filtered, and DCM was removed by rotary evaporation to obtain the product 3.5.
[0100]
[0101] S1-6, mix 10 mmol of 3.5 and 4 mL of 6 M hydrochloric acid (HCl) aqueous solution, stir and react at room temperature for 12 h, then add 20 mL of saturated ammonium hexafluorophosphonate (NH4PF6) aqueous solution and 60 mL of acetone, stir and react at room temperature and 500 rpm for 6 h, filter the resulting precipitate, and perform column purification (eluent DCM:MeOH=100:1 v / v) to obtain a hydroxyl-containing daisy chain, and the resulting product is named 3.6.
[0102]
[0103] The prepared product 3.6 1 H NMR spectrum ((CD3)2S=O, 298K, 400MHz) Figure 4 As shown, mass spectrum (HRMS) Figure 5 shown.
[0104] 1 H NMR ((CD3)2S=O, 298K, 400MHz) δ (ppm): 7.57 (dd, J=8.5, 1.9Hz, 1H), 7.46 (d, J=1.9Hz, 1H), 7.37 (d, J=8.4Hz, 2H), 7. 09(d,J=8.6Hz,1H),6.97(d,J=8.5Hz,2H),4.23(t,J=6.5Hz,2H),4.17(t,J=3.8Hz,2H),4.13(t,J=4.0Hz,2H),4.01( s,2H),3.96(t,J=6.4Hz,2H),3.80-3.77(m,4H),3.64-3.61(m,4H),3.58-3.55(m,4H),3.84-3.48(m,12H),3.37(t,J =6.4Hz,2H),2.81(t,J=7.7Hz,2H),1.73-1.66(m,4H),1.56(t,J=5.9Hz,2H),1.41-1.37(m,6H),1.33-1.23(m,20H).
[0105] HRMS: m / z calcd for C 48 H 80 NO 12 ,862.5675[M-PF6] + ; found 862.5672[M-PF6] + .
[0106] S2. Preparation of mechanically interlocked polymers
[0107] 400 mg of mechanical interlocking molecules were dissolved in 20 mL of dichloromethane, and 200 mg of N,N'-carbonyldiimidazole was added. The mixture was stirred at 25°C and 500 rpm for 20 hours. After the reaction was completed, the reaction system was repeatedly washed with water for 3-5 times, and then dried with anhydrous magnesium sulfate to remove water. Finally, dichloromethane was removed to obtain a mechanical interlocking polymer. The reaction was as follows:
[0108]
[0109] like Figure 6As shown in the 7.0-8.3 ppm H NMR spectrum of the daisy chain-based mechanical interlocking polymer, the three characteristic signal peaks of the imidazole group are 1 , H 2 , H 3 They appeared at 8.23 ppm, 7.56 ppm and 7.06 ppm, respectively, thus proving the presence of an ester functional group with an imidazole group in the daisy chain-based mechanically interlocked polymer.
[0110] S3. Dissolve 25 mg of the mechanical interlocking polymer prepared in S2 in 5 mL of N,N-dimethylacetamide, take 5 mL to soak the titanium carbide film, soak it in a 35°C environment for 10 hours, and extract to obtain a daisy chain polymer bridged titanium carbide film, wherein the titanium carbide film is selected to be consistent with that in Example 1.
[0111] The extraction method is: wash the polymer-bridged titanium carbide film obtained in S3 with anhydrous ethanol, and dry it in a vacuum oven at 45°C for 4 hours, wherein the vacuum degree of the vacuum oven is: -0.1MPa, to obtain a daisy chain polymer-bridged titanium carbide film, marked as: DBM.
[0112] Example 4
[0113] This embodiment provides a method for preparing a stretchable electroluminescent device using a RBM film, such as Figure 7 As shown, including:
[0114] The bottom layer is the RBM film layer, the middle layer is the zinc sulfide / copper / polydimethylsiloxane (ZnS:Cu / PDMS) composite material layer, and the top layer is the polydioxyethylthiophene (PEDOT) layer. The layers are combined by spin coating and then hot pressing. The specific steps are: first, the RBM film is flattened on the glass, and then the ZnS:Cu / PDMS composite material is spin coated at 3000rpm for 30s to coat the RBM film, and then the ZnS:Cu / PDMS is thermally cured at 80℃ for 1h. Then, the top electrode of the PEDOT layer is spin coated at 2000rpm for 30s, dried at 100℃ for 15min, and finally, the upper and lower layers of the electrode are connected with copper foil, and an AC power supply is connected. The principle of luminescence is: when the AC power is turned on, an electric field will be formed between the upper and lower electrodes, and ZnS:Cu is an electroluminescent phosphor that will emit bright blue light under the excitation of the electric field. Therefore, when the AC power is turned on, the device will emit light.
[0115] Comparative Example 1
[0116] The steps of this comparative example are basically the same as those of Example 1, except that:
[0117] By replacing [2]rotaxane with heptaethylene glycol and keeping other conditions unchanged, a heptaethylene glycol-bridged titanium carbide film was obtained, which was marked as: HBM.
[0118] Comparative Example 2
[0119] The steps of this comparative example are basically the same as those of Example 1, except that:
[0120] Step S2 is omitted, and the mechanically interlocked molecule [2]rotaxane in step S1 is directly used in step S3 to replace the mechanically interlocked polymer in S3, thereby obtaining a titanium carbide film containing [2]rotaxane without the participation of N,N'-carbonyldiimidazole, which is labeled as: RBM-NOCDI.
[0121] Comparative Example 3
[0122] This comparative example is a pure titanium carbide film, that is, the titanium carbide film used in the above embodiments and comparative examples, which is a titanium carbide self-supporting film material (Ti3C2T x ), where T x Represents surface hydroxyl (-OH) functional groups, with a thickness of 5 μm and labeled as: MXene.
[0123] Detection and analysis
[0124] The performance testing and analysis of the above-mentioned embodiments and comparative examples are described below.
[0125] 1. Flexible detection
[0126] The RBM film is bent, as shown in Figure 8 As shown, the film is not damaged after bending, indicating that the film is flexible.
[0127] 2. SEM and EDS testing
[0128] The cross-section of the RBM film was observed using SEM (test voltage was 5 kV), as shown in Figure 2. Fig. 9 As shown in (a), it can be seen that the cross section is stacked layer by layer; using EDS to analyze the surface of the RBM film, as shown in Figures (b) to (d), it can be seen that nitrogen is evenly dispersed like titanium and carbon, indicating that [2]rotaxane is evenly dispersed in the film. The EDS energy dispersive spectrum is obtained by using a field emission scanning electron microscope (Apreo 2S) from FEI Company at an accelerating voltage of 5kV to first obtain a scanning electron microscope SEM image, and at the same time record the EDS spectrum to detect the element distribution.
[0129] 3. Mechanical properties testing
[0130] The tensile stress and strain test (tensile rate is 1 mm / min) was performed on the samples prepared in Examples 1 to 3 and Comparative Examples 1 to 3. Fig.10 and Fig.11 As shown, it can be seen that Fig.10 As shown in Figure 2, the mechanical properties of the RBM film are better than those of the HBM and MXene films, indicating that the presence of [2] rotaxane improves the performance of the titanium carbide film, which further illustrates that mechanically interlocked molecules can be used to prepare enhanced and toughened titanium carbide film materials; Fig.11 As shown in the figure, the mechanical properties of the RBM film are significantly better than those of the RBM-NOCDI film, indicating that the participation of N,N'-carbonyldiimidazole is crucial. It can react with the hydroxyl groups of [2]rotaxane and the hydroxyl groups on the surface of the titanium carbide film, thereby cross-linking the [2]rotaxane with the titanium carbide film.
[0131] The tensile stress-strain curves of the mechanically interlocked polymer bridged titanium carbide films prepared in Example 2 and Example 3 are shown in FIG. Fig.12 As shown, it can be seen that the films prepared in these two embodiments also have excellent mechanical properties.
[0132] The RBM film prepared in Example 1 was subjected to cyclic stretching test. Fig.13 As shown, it can be seen that the RBM film can be cycled at least 500 times in the strain range of 0% to 15%, and the film exhibits a constant and reversible resistance change, confirming that the RBM film has excellent fatigue resistance and can still have stable conductivity while being repeatedly stretched.
[0133] 5. Stretching-luminescence performance combined test
[0134] The stretchable electroluminescent device prepared in Example 4 was tested. Fig.14 As shown, it can be seen that the brightness of the luminescence remains basically unchanged when the elongation increases from 0% to 20%, further confirming the high elongation of the RBM film.
[0135] In summary, the present invention utilizes the unique intramolecular motion of mechanical interlocking molecules to prepare titanium carbide films with high elongation (about 20%) and cyclic stretchability (elongation within 15%), which is beneficial to the application of titanium carbide films in the field of flexible electronics. The required mechanical interlocking molecules can be designed as needed, so this method has universal applicability.
[0136] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a mechanically interlocked polymer reinforced and toughened titanium carbide film material, characterized in that: The preparation method comprises the following steps: S1. determining raw materials, including: mechanical interlocking molecules and copolymers, wherein the mechanical interlocking molecules contain one or more hydroxyl functional groups; S2, reacting the mechanical interlocking molecules with the copolymer to extract a mechanical interlocking polymer; S3, dissolving the mechanical interlocking polymer in an organic solvent to prepare a soaking solution, placing the titanium carbide film in the soaking solution for soaking treatment, and extracting to obtain the mechanical interlocking polymer bridged titanium carbide film.
2. The method for preparing the mechanically interlocked polymer reinforced and toughened titanium carbide thin film material according to claim 1, characterized in that: It also includes one or more of the following technical features: A. The copolymer is selected from N,N'-carbonyldiimidazole; B. The titanium carbide film is a self-supporting film prepared by vacuum filtration of a titanium carbide aqueous solution.
3. The method for preparing the mechanically interlocked polymer reinforced and toughened titanium carbide thin film material according to claim 1, characterized in that: The mechanically interlocked molecules are one or more of rotaxanes, catenanes, and daisy chains.
4. The method for preparing the mechanically interlocked polymer reinforced and toughened titanium carbide thin film material according to claim 1, characterized in that: It also includes one or more of the following technical features: In A and S2, the mechanical interlocking molecules and the copolymer react in a reaction solvent, and the reaction solvent is selected from dichloromethane, chloroform, toluene, tetrahydrofuran, acetonitrile, and N,N-dimethylformamide; In B and S3, the organic solvent is selected from one or more of tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, dichloromethane, chloroform, and dimethyl sulfoxide.
5. The method for preparing the mechanically interlocked polymer reinforced and toughened titanium carbide thin film material according to claim 1, characterized in that: It also includes one or more of the following technical features: A. The ratio of the mechanically interlocked molecules to the reaction solvent is: (100-500) mg: (10-20) mL; B. The ratio of the mechanically interlocked molecules to the copolymer is: 1 mol: (10-20) mol; C. The concentration of the mechanical interlocking polymer in the soaking solution is 3 to 10 mg / mL; D. The thickness of the titanium carbide film is 3 to 10 μm; E. The dosage ratio of the titanium carbide film and the immersion solution is: (15-20) mg: (4-6) mL.
6. The method for preparing the mechanically interlocked polymer reinforced and toughened titanium carbide thin film material according to claim 1, characterized in that: It also includes one or more of the following technical features: A. The mechanically interlocked molecules and the copolymer react in a reaction solvent under the following reaction conditions: stirring at room temperature, a stirring speed of 400 to 600 rpm, and a reaction time of 12 to 24 hours; B. The soaking treatment is: soaking at 20-40°C for 6-12 hours.
7. The method for preparing the mechanically interlocking polymer reinforced and toughened titanium carbide thin film material according to claim 1, characterized in that: It also includes one or more of the following technical features: A. In S2, the mechanical interlocking polymer is extracted by washing the reaction system of S2 with water for multiple times, removing water with anhydrous magnesium sulfate, and then removing dichloromethane; In B and S3, the mechanically interlocked polymer bridged titanium carbide film is extracted by washing with anhydrous ethanol and then drying the film. The drying temperature is 40 to 60° C. and the film is vacuum dried for 2 to 4 hours.
8. A mechanically interlocked polymer reinforced and toughened titanium carbide film material, characterized in that: The thin film material is prepared according to the method according to any one of claims 1 to 7, the surface of the thin film material is bridged with a mechanical interlocking polymer, and the mechanical interlocking polymer contains an ester functional group with an imidazole group.
9. A use of the mechanically interlocking polymer reinforced and toughened titanium carbide film material according to claim 8, characterized in that: The film material is applied to electronic products, wearable intelligent devices, and wearable rehabilitation equipment.
10. The use of the mechanically interlocking polymer reinforced and toughened titanium carbide thin film material according to claim 9, characterized in that: The thin film material is applied to a stretchable electroluminescent device.
Citation Information
Patent Citations
Two-dimensional titanium carbide film with stable environment and excellent electrical conductivity and mechanical property as well as preparation method and application thereof
CN112795209A
MXene nanosheet film as well as preparation method and application thereof
CN115231833A
Preparation method of mechanically-interlocked high-performance titanium carbide composite conductive fiber
CN115537972A
High-performance MXene-based fiber and preparation method thereof
CN118547396A
High-sensitivity MXene-based sensing fiber as well as preparation method and application thereof
CN118727194A